2017
DOI: 10.1212/cpj.0000000000000397
|View full text |Cite
|
Sign up to set email alerts
|

Progression and effect of cognitive-behavioral changes in patients with amyotrophic lateral sclerosis

Abstract: Cognitive-behavioral change is a key aspect of disease heterogeneity in ALS. Executive function in ALS overall remains stable over 7 months as detected by an administered screening tool. However, patients may develop caregiver-reported behavioral symptoms in that time period. Screening for caregiver-reported symptoms has a particular utility in predicting future clinical decline, increased caregiver burden, and worsening patient QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 40 publications
0
24
2
Order By: Relevance
“…Indeed, nearly two-thirds of cases had some evidence of cognitive impairment in more advanced stages. In contrast to previous publications, [2][3][4][5][6][7] our data point to a correlation between the severity of motor impairment and the severity of cognitive deficits, and suggest that cognitive function may not remain stable in patients with ALS. Importantly, our data indicate that the presence of bulbar signs is strongly associated with more severe cognitive impairment at all stages of disease.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Indeed, nearly two-thirds of cases had some evidence of cognitive impairment in more advanced stages. In contrast to previous publications, [2][3][4][5][6][7] our data point to a correlation between the severity of motor impairment and the severity of cognitive deficits, and suggest that cognitive function may not remain stable in patients with ALS. Importantly, our data indicate that the presence of bulbar signs is strongly associated with more severe cognitive impairment at all stages of disease.…”
Section: Discussioncontrasting
confidence: 99%
“…Amyotrophic lateral sclerosis (ALS) can no longer be considered a disease limited to the motor system but rather a multisystem disorder that involves cognitive domains in at least half of the cases. 1 Longitudinal studies point to a relative stability of cognitive function in patients who are not impaired at first examination, and a progression of the impairment in patients already compromised, [2][3][4][5][6][7] although such studies are complicated by the progressive loss of speech and motor function in the hands that hinders the accuracy of neuropsychological testing and causes a high patient attrition rate, further complicating our ability to evaluate the pattern of cognitive impairment in patients with ALS over time. 2,3 A recent study performed on a cross-sectional clinical-based cohort of patients evaluated using the Edinburgh Cognitive and Behavioural ALS Screen (ECAS) has shown that cognitive and behavioural deficits are more frequent and severe with advanced disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive impairment in ALS is widely regarded as a negative prognostic indicator and linked to reduced survival ( 17 , 18 , 213 ). Neuropsychological deficits in ALS are thought to be associated with increased caregiver burden ( 214 , 215 ) and reduced quality of life ( 216 ). The recognition of the far-reaching effects of neuropsychological deficits on nearly all aspects of ALS care, caregiver support, resource allocation, and prognosis, led to the inclusion of specialist neuropsychologists as core members of ALS multidisciplinary teams worldwide ( 217 , 218 ).…”
Section: Relevance To Clinical Carementioning
confidence: 99%
“…To date there is no cure and treatment mainly aims to improve or sustain quality of life (QoL) for the patients. Various factors influence QoL and health-related QoL in ALS, including disease progression, depression, anxiety, pain and dysphagia [[3], [4], [5], [6]]. There is a link between mental health and physical health, and many studies showed that psychological factors are related to the course and severity of several physical diseases [7].…”
Section: Introductionmentioning
confidence: 99%